Investigation of firefly algorithm and chaos firefly algorithm for load prequency control / Zaid Najid - Zaid, Najid (2015)
The changes of the structure of the power system, size, and complexity have increased the important of LFC. For this reason, this research studies the controller aspect of LFC by using the Fractional Order Integral-Derivative (FOID) controller or IλDμ Controller. In order to obtain the best controller parameter values for LFC, Firefly Algorithm (FA) and Chaos Firefly Algorithm (CFA) are used. This project analyzes the performance of the algorithms based LFC in three power system area. The primary objectives of LFC are to maintain frequency and minimize power interchanges with neighboring control areas. These objectives are met by measuring a control error signal called the area control error (ACE), which calculates the real power difference between generation and load. In this project, the integral of time multiply squared error (ITSE) as the objective function is used on the ACE. The model of the system is designed using Matlab software to carry out simulation studies. Step input load deviation is injected to the system at designated location and the optimization of ramp rate, speed regulation and the IλDμ parameters are carried out. The frequency deviation and tie line power changes characteristics are analyzed to observe the system performance. The maximum overshoot, settling time and ITSE value is also recorded and compared. Result shows that the CFA is the best optimization method due to its robustness and consistency. The project can be further improved by tuning the controller using other optimization techniques and including other physical constraints.